Arab Society: A Compendium of Social Statistics - Issue No. 11 - United Nations Economic; Social Commission for Western Asia (United Nations, 2014)
The Compendium of Social Statistics and Indicators is a biennial publication published by the Statistics Division of the Economic and Social Commission for Western Asia (ESCWA). It typically focuses on such areas as population, education, households and family, human settlements, health and economic activity. In the hope of widening the audience of this publication, the eleventh issue is intended not only as a reference for policymakers and other officials, but also as a snapshot of trends in the region for readers with an interest in the social climate of Western Asia, including academics, students, journalists and the general public.